Characterization of source plasma from self‐identified vaccinated or convalescent donors during the 2009 H1N1 pandemic. Issue 5 (15th February 2018) - Khalenkov, Alexey; He, Yong; Reed, Jennifer L.; Kreil, Thomas R.; McVey, John; Norton, Malgorzata; Scott, John; Scott, Dorothy E.
Abstract : BACKGROUND: Influenza immune globulin, manufactured from plasma of convalescent or vaccinated donors has been proposed as a potential therapy for severe influenza. In 2009, a program was initiated to collect plasma from donors who self‐identified as having had H1N1 influenza or having received the H1N1 pandemic vaccine. The goal of this study was to determine the efficiency of donor screening by self‐identification without antibody testing, and to evaluate demographic predictors of high‐titer donations. STUDY DESIGN AND METHODS: Plasma samples from self‐identified or control donors were randomly selected to evaluate hemagglutination inhibition (HAI) antibody responses. HAI titers were correlated with donor age, gender, location, and influenza exposure history. RESULTS: Both self‐identified vaccinated and convalescent donor groups had higher geometric mean titers (GMTs) against A/California/07/2009 (H1N1) virus compared to the control donors (39.9, 24, and 8.5, respectively). The proportion of samples with titers ≥64 in vaccinated, convalescent, and control donors were 54%, 37%, and 10%, respectively. Donations with titers ≤16 were predominant in control donors (80%) and substantial in convalescent (47%) and vaccinated (40%) donors. Titers did not correlate with donor age, gender, or geographical location. GMTs for vaccinated donors were significantly higher than for convalescent donors and in both groups significantly higher than in the control. CONCLUSION: Targeted collection of plasma containing high levels of anti‐influenza antibodies from self‐identified donors was effective, but could be further improved by reducing the number of low‐titer donations. More selective donor screening and/or testing for influenza antibodies could increase the potency of an influenza antibody‐rich immune globulin (FLUIGIV).